Foucauldian Theoretical Power Relations in Alban Berg’s Operas - Ljubibratic, Vanja (Interdisciplinary Studies in Musicology, 2023)
The narratives of Alban Berg’s two operas, Wozzeck and Lulu, have often been analyzed for their socio-cultural symbolisms as reflections of the artistic movements in which they were composed. However, the operas also display a myriad of complex interpersonal relationships between the characters that bear explicit associations with themes of power. Michel Foucault famously devised several theories on power, through which this article aims to filter Berg’s operatic narratives in order to draw unique parallels between social theory and artistic expression. What emerges is an interdisciplinary study that expands the understanding of these works through this unique juxtaposition, yielding new interpretations of these characters’ interactions through the applicable theories of Foucault’s force relations.